Experimental demonstration of Fabry-Perot open resonators in a surface-wave bandgap crystal - Gao, Zhen (2017)
We report on the proposal and experimental realization of a type of retardation-based Fabry-Perot (FP) open resonator in a surface-wave bandgap crystal implemented on a single structured metal surface. This surface-wave FP open resonator is formed by introducing a finite line defect in the surface-wave bandgap crystal, whose resonance frequencies lie exactly within the forbidden bandgap of the surrounding crystal. Due to the complete surface-wave forbidden bandgap, a new FP plasmonic resonance mode exhibiting monopolar features which is missing in both traditional FP resonators and plasmonic resonators is emerged. Near-field response spectra and imaged mode profiles are presented to characterize the properties of these FP open resonators in the microwave regime.